Innovation outlook : renewable methanol - Kang, Seungwoo (International Renewable Energy Agency, 2021)
Methanol is essential for the chemical industry and represents an emerging fuel for a wide range of uses. Although largely produced from fossil fuels, it can also be made from sustainable, renewable-based energy sources. The need to mitigate climate change and eliminate carbon dioxide (CO2) emissions from all kinds of energy use has prompted rising global interest in renewable methanol. The shift to such types - derived from biomass or synthesised from green (renewable-based) hydrogen and CO2 - could expand methanol's use as a chemical feedstock and help to make industry and transport fuels carbon neutral. Costs for renewable methanol are currently high, while production volumes are low. But with the right policies, renewable methanol could become cost competitive by 2050 or earlier. This outlook from the International Renewable Energy Agency (IRENA) and the Methanol Institute identifies challenges, offers policy recommendations and explores ways to produce renewable methanol at a reasonable cost. Chemical and plastic industries - which currently use about two-thirds of all methanol - particularly need this to cut their process emissions.